Effects of periodical starvation on growth and muscle composition in fingerlings of Labeo bata (Hamilton, 1822) - Das, Hiramoni; Das, Sudhir Kumar; Bhakta, Dibakar (Journal of the Inland Fisheries Society of India, 2019)
A study was conducted to find out impact of periodical starvation on growth of fingerlings of Labeo bata (Hamilton, 1822) with four sets of experiments in triplicates for a period of 60 days. The treatments were designated as the control (fed every day), D1 (one day starvation + 2 days feeding), D2 (2 days starvation + 2 days feeding) and D3 (3 days starvation + 2 days feeding). There was no significant difference in weight gain and specific growth rate (weight) between the treatment D1 and control though feed consumption was considerably low. It indicated that one day of feed deprivation followed by two days of satiation feeding can compensate the growth in Labeo bata. However, such values were lower compared to control in treatment D2 indicating partial compensation. The muscle composition did not exhibited significant difference in nutrient level between control and D1 though it was significant in protein and lipid level in treatments D2 and D3. It indicated that one day of skipping the feeding with two days of subsequent satiation feeding in cyclic manner can reduce feed consumption substantially without compromising the growth in fingerlings of Labeo bata. Keywords Growth compensation, starvation, Labeo bata.